RANCANG BANGUN APLIKASI E-COMMERCE FURNITUR BERBASIS ANDROID - Jamilah Jamilah; Arif Ali Ibrahim (Jurnal Ilmiah Teknik, 2023)
Furniture sales has become one of the good business opportunities, but the challenges facing manufacturers today are the growing number of competitors and the scope of marketing and sales as well as the place to interact between the seller and the buyer is limited. The research aims to create an e-commerce furniture application that can be used as a means of selling furniture online using the Internet network and Android-based application platforms. The application is based on the waterfall method. The application is built with the Flutter and Dart frameworks, while the admin backend uses the Laravel 8 framework with PHP. The research resulted in an Android-based e-commerce app consisting of home menu, products, product details, payment details, orders and payments. Based on the tests carried out using blacbox testing showed the application can run as expected. Based on the device testing using 4 smartphones, the app can run on all the devices that are used well.